EFL Students’ Common Errors in L2 Writing - Amalia, Nurul Halisa; Syukri, Suhartini; Zur, Sarjaniah (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2024)
The purpose of this study is to investigate common errors that often occur in student writing The researcher used a qualitative design to explain and explore this research. The data was gathered from the students of first grade class of accounting at one of senior high school in Southeast Sulawesi, Indonesia and the number of samples was eight students out of thirty-four students. There is one type of instrument that is document of writing in recount text. It was used to collect this research data. The result showed that that there are some errors that often occur in student writing. However, in this study only took the four most common errors made by students especially in the form of words, punctuation, and capitalization and word choices. This study provides suggestion for teachers and students to improve teaching and learning process in the class.